Venomics of Trimeresurus (Popeia) nebularis, the Cameron Highlands Pit Viper from Malaysia: Insights into Venom Proteome, Toxicity and Neutralization of Antivenom - Tan, Choo Hock; Tan, Kae Yi; Ng, Tzu Shan; Quah, Evan S.H.; Ismail, Ahmad Khaldun; Khomvilai, Sumana; Sitprija, Visith; Tan, Nget Hong (MDPI, 2019)
Trimeresurus nebularis is a montane pit viper that causes bites and envenomation to various communities in the central highland region of Malaysia, in particular Cameron’s Highlands. To unravel the venom composition of this species, the venom proteins were digested by trypsin and subjected to nano-liquid chromatography-tandem mass spectrometry (LC-MS/MS) for proteomic profiling. Snake venom metalloproteinases (SVMP) dominated the venom proteome by 48.42% of total venom proteins, with a characteristic distribution of P-III: P-II classes in a ratio of 2:1, while P-I class was undetected. Snaclecs constituted the second most venomous protein family (19.43%), followed by snake venom serine proteases (SVSP, 14.27%), phospholipases A 2 (5.40%), disintegrins (5.26%) and minor proteins including cysteine-rich secretory proteins, L-amino acid oxidases, phosphodiesterases, 5 ′ -nucleotidases. The venomic profile correlates with local (painful progressive edema) and systemic (hemorrhage, coagulopathy, thrombocytopenia) manifestation of T. nebularis envenoming. As specific antivenom is unavailable for T. nebularis, the hetero-specific Thai Green Pit viper Monovalent Antivenom (GPVAV) was examined for immunological cross-reactivity. GPVAV exhibited good immunoreactivity to T. nebularis venom and the antivenom effectively cross-neutralized the hemotoxic and lethal effects of T. nebularis (lethality neutralizing potency = 1.6 mg venom per mL antivenom). The findings supported GPVAV use in treating T. nebularis envenoming. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.